OPTIMAL STRATEGIES FOR IMPLEMENTING MULTIDISCIPLINARY AND TRANS DISCIPLINARY EDUCATION IN MANAGEMENT PROGRAMS: INSIGHTS FROM GOAN COLLEGES - Barreto, Nigel; Silveira, Cedric (International Journal of Research -GRANTHAALAYAH, 2024)
This study looks into the factors that influence the quality of management education offered by Goa-based institutes by using a thorough examination of important variables. It provides detailed insights through the use of data on interdisciplinary research centres, faculty cooperation, interdisciplinary electives, cross-institutional relationships, and experiential learning opportunities. The results highlight a paradigm shift towards comprehensive and contextually appropriate educational frameworks by revealing a greater emphasis on faculty partnerships, cross-departmental teaching, practical engagement or experimental learning possibilities, and integrated curriculum creation. Remarkably, multidisciplinary research institutes show unrealized promise, possibly due to the expense associated with them. This study offers practical suggestions for Goan educational institutions to improve their curricula while yet being adaptable to changing business needs and worldwide patterns. It contributes to the conversation on management education by providing suggestions for promoting academic excellence through multidisciplinary studies, experiential learning, and strategic alliances.